PENGARUH RELIGIUSITAS, STATUS SOSIAL EKONOMI, LOVE OF MONEY DAN GENDER TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI (Studi Kasus di satu PTN dan dua PTS di Malang) - Ulfa Kasanatul Munawaroh; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis research was conducted to see the influence of religiosity, socioeconomic status, love of money, and gender on the ethical perceptions of accounting students. In this study, the authors took a sample of active students of accounting study program class of 2016, faculty of economics and business, Malang Islamic University, Malang State Islamic University Maulana Malik Ibrahim and Malang Muhammadiyah University, accounting students who have taken business and professional ethics courses. The analysis method used is multiple linear regression. Based on the results of the tests that have been done, that the variables of religiosity, socioeconomic status, love of money and gender affect the ethical perceptions of accounting students at the Islamic University of Malang, the State Islamic University of Maulana Malik Ibrahim Malang and the University of Muhammadiyah Malang. The results partially show that the variable of religiosity has a positive effect on the ethical perceptions of accounting students, socioeconomic status has a negative effect on ethical perceptions of accounting students, love of money has a negative effect on ethical perceptions of accounting students and gender has no effect on ethical perceptions of accounting students.Keywords: Religiosity, Socio-Economic Status, Love of Money, Gender, Ethical Perception.